2018
DOI: 10.1200/jop.18.00031
|View full text |Cite
|
Sign up to set email alerts
|

Documenting Goals of Care Among Patients With Advanced Cancer: Results of a Quality Improvement Initiative

Abstract: Our QI initiative was successful in improving rates of GOC documentation in patients with advanced cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…In this cohort of patients, pre‐study GOC completion rate was high compared to other studies, 18,24 albeit in keeping with previous inpatient studies from our centre 20 . The combination of a communication skills refresher course and verbal prompting of the patients' current GOC improved documentation of GOC during routine clinic reviews of patients with advanced lung cancer.…”
Section: Discussionsupporting
confidence: 82%
“…In this cohort of patients, pre‐study GOC completion rate was high compared to other studies, 18,24 albeit in keeping with previous inpatient studies from our centre 20 . The combination of a communication skills refresher course and verbal prompting of the patients' current GOC improved documentation of GOC during routine clinic reviews of patients with advanced lung cancer.…”
Section: Discussionsupporting
confidence: 82%
“…Our initiative adds to other communication interventions (prompts, different templates, and order sets) recently described in modern EHRs. 34,35 In a prior study, 36 GOC documentation was found to increase during a quality improvement initiative that included email reminders to physicians as well as a scorecard to display overall and individual physician rates of GOC documentation. We did not use these strategies, although encouragement by departmental leadership, as well as anticipated and real worsening of patients' health status with COVID-19 infection, may have contributed to increases we saw in GOC documentation on our new GOC template during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Following the intervention, there was an increase in documented GoCCs from 20.5% for the control group versus 44.6% in the intervention group. More recently, use of email reminders to 9 medical oncologists, to identify 184 high-risk patients, also resulted in an increase in documentation of GoCCs from 0% to 29% (Karim et al, 2018).…”
Section: Discussionmentioning
confidence: 99%